NUTRITIONAL STATUS AND ASSOCIATED FACTORS IN CHILDREN AGED 5-10 YEARS AT THE NATIONAL CHILDREN’S HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: Describe the nutritional status of children aged 5-10 years at the Nutrition Clinic, National Children’s Hospital; assess several factors associated with the nutritional status of these children.Subject and methods: Cross-sectional description.Results: Children with underweight malnutrition accounted for 31.9%, stunting 21.3%, wasting 16.9%, and overweight/obesity 5.5% with no significant difference between sexes. Children with low birth weight had 3.7 times higher odds of being underweight and 4.7 times higher odds of being wasted compared to those with normal birth weight. Both paternal and maternal heights were significantly associated with the child’s height-for-age, with the effect of maternal height (β = 0.199; p = 0.001) being stronger than that of paternal height (β = 0.178; p = 0.004), there is a difference between boys and girls. The habit of skipping breakfast increases the risk of stunting in children by 8.3 times, while children who eat quickly are 8.4 times more likely to be overweight or obese compared to those who eat slowly.Conclusion: The prevalence of malnutrition among children aged 5-10 years remains high in all three forms, requiring appropriate and timely nutritional interventions to improve their growth and development.
Keywords: Nutritional status, children aged 5-10 years, factors associated with malnutrition, overweight-obesity